The Influence of Student Participation in Scouting Extracurricular Activities on Spatial Thinking Skills and Disciplined Character at MTs Mathla'ul Anwar 2, Bogor City - Imas Nursa'adah; Samadi Samadi; Sucahyanto Sucahyanto (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
Based on the facts on the ground, there is still significant variation in student participation in the mandatory Scouting extracurricular activity. Some students are actively involved, while others are passive or even do not participate at all. This raises the question of whether the level of participation in Scouting can significantly contribute to the development of students' character and abilities. This study aims to analyze the influence of student participation in Scouting extracurricular activities at MTs Mathla'ul Anwar 2, Bogor City. The method used in this study is a quantitative descriptive method with percentages. The sample size was 120 students, with 60 active students and 60 inactive students. The instruments used were test questions, questionnaires, and observation sheets. The results showed that students with high levels of active participation scored moderately to very high in spatial thinking ability and disciplinary character assessments. This means that the level of participation in Scouting extracurricular activities influences students' spatial thinking ability and disciplinary character.